Features of styrene copolymerization with vinylbenzyl trimethylammonium chloride in solvents of different polarities - E. V. Dolgova; M. G. D’yakova; V. A. Tverskoy (Тонкие химические технологии, 2014)
The solution copolymerization of styrene with vinylbenzyl trimethylammonium chloride (VBTMAC) was investigated. The solvents used in this study form homogeneous solutions with mixtures of monomers and possess different polarity, namely, isopropanol, DMSO, and their mixtures. Reactivity ratios of the copolymerization of these monomers in isopropanol were determined: rstyrene is 0.15 ± 0.01, rVBTMAC is 0.46 ± 0.004. Based on the values of the reactivity ratios authors conclude that the resulting copolymers have a tendency to alternate structural units. It was shown that the copolymerization of these monomers could not be described by means of Mayo-Lewis copolymerization model. The main reason for the deviation from the classical scheme of copolymerization is the bootstrap effect (the selective sorption of growing polymer radical by styrene). This effect increases with increasing polarity of the solvent as well as when the resulting copolymers are allocated in heterophase.